Methodological bases of agroecological optimization and determination of the integrated indicator of the ecological state of Poltava region in the system of sustainable development of agricultural territories - Ласло, О. О.; Диченко, О. Ю.; Нагорна, С. В. (Scientific Progress & Innovations, 2018)
The article considers the expediency and necessity of agroecological optimization and determination of the integral index of the ecological state of Poltava region. The presented results of the research prove that the methodology for determining the integral index of the condition of Poltava region in the system of sustainable development of residential territories gives an opportunity to optimize the territory of the region for the production of organic products. To achieve the goal, scientists’ methods are used to make a ranking and establish criteria for anthropogenic impact on the environmental state of the environment.